If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y+3=-20
We move all terms to the left:
y+3-(-20)=0
We add all the numbers together, and all the variables
y+23=0
We move all terms containing y to the left, all other terms to the right
y=-23
| x=−4x+10≥5x+55 | | 12.5-4x=-2x-2.5 | | -2(5+6y)+16=-90 | | x-(-13)=-9 | | 3x-27=133 | | -8w+2(w+5)=-8 | | -8-7x=-20.5 | | x.15=46 | | 48/4=9/b | | -5(-5k-4)=170 | | 2(x-3.70)=5.80 | | 2/5y-1/10=3/5 | | x+5/2+x=3x-2(3x+1) | | 25-13x=22.66 | | 73=-6r | | 8^(x-3)-15=389 | | 5(8a+1)=125 | | h+30=64 | | 9x+6=x+86 | | X+2z=402 | | 15h-0.17(15h)=460.65 | | -3x-5=2(x-10) | | 3x-39=-18-2x | | k+22=10 | | 3/4*x+5=-9 | | 90-8.41x=64.77 | | 9k–3=78 | | q÷7=40 | | 12-n+10=18-5n | | 8u-10=-50 | | -2x-34=5(x+3) | | t+24=-16 |